Prevalence of Selfitis among Nursing Personnel in Ranchi - Begum, Farzana (Journal of Pharmacy Practice and Community Medicine)
Background: Advent of social networking has changed the entire communication system. People have become more expressive and opinionated. It is also used to fulfil individuals’ identity need, typically, those suffer from a lack of self-confidence and are seeking to ‘fit in’ with those around them.[1] Therefore some people take selfies and continually posts them on social media to get online appreciation in the form of ‘likes’ and ‘comments’. Psychologists have warned that ‘selfitis’ is an ailment that needs attention and people who suffer from this need help. Objectives: To explore the prevalence of selfitis among nursing personnel and their purpose of taking selfie. Methods: : This is a cross sectional analysis of data collected from 444 nursing personnel from selected hospitals of Ranchi city with the help of selfitis behaviour scale. Data were evaluated through frequency and percentage. Results: Sixty-nine percent nursing personnel suffering from acute selfitis, whereas 21% chronic and 10% borderline. Among them 67% like to take selfies sometimes, 26% rarely and 7% regularly take selfies. Conclusion: Though selfitis is not yet recognised as a problem officially, not included in DSM – 5 yet, but any obsession is a real problem and leads to negative impact, therefore efforts should be taken to increase awareness and prevent such issue.
Keywords: Prevalence; Selfitis; Nursing; Students; Ranchi